2015
DOI: 10.1167/iovs.15-16719
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness Evaluation Before and After Hemodialysis in Patients With and Without Diabetes

Abstract: The current results may reflect that systemic fluid accumulation has a greater effect on the diabetic choroid, probably due to damage to the choroidal vasculature, in patients with ESKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…Other studies showed opposing results in patients with and without DM, showing decreased SFCT after HD [26][27][28][29]. In some studies, further subgroup analysis showed significantly larger SFCT changes in the patients with DM than in those without [28,29]. The results of current study are consistent with these studies and support the hypothesis that DM and its effect on choroidal vasculature can lead to significant changes in SFCT after HD.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Other studies showed opposing results in patients with and without DM, showing decreased SFCT after HD [26][27][28][29]. In some studies, further subgroup analysis showed significantly larger SFCT changes in the patients with DM than in those without [28,29]. The results of current study are consistent with these studies and support the hypothesis that DM and its effect on choroidal vasculature can lead to significant changes in SFCT after HD.…”
Section: Discussionsupporting
confidence: 86%
“…One study suggested that body weight loss and changes in serum osmolarity and SBP were significantly correlated with SFCT changes after HD [28]. Another study suggested that amount of body fluid removal was significantly correlated with the SFCT in patients without DM, but no in those with DM [29]. The results of our study showed that DM was the only factor significantly correlated with SFCT changes after HD.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations